Experimental and Clinical Experience with an IM Pin External Skeletal Fixator Tie-in Configuration - Aron, D. N.; Foutz, T. L.; Keller, W. G.; Brown, J. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
An intramedullary (IM) pin external skeletal fixator “tie-in” configuration is described, for use as a stabilizing device, in the treatment of fractures of the humerus and femur in the dog and cat. With in vitro testing of the configuration using cadaver bones, more resistance to bending was gained by the tie-in arrangement than was possible with one not tied-in. Forty-one clinical cases documented the use of the tie-in configuration for fracture repair. Twenty-four dogs and 17 cats were treated over the past seven years. Fourteen were used to stabilize fractures of the humerus and 27 for the femur. Migration of the IM pin or external fixation frame was not seen and all of the cases went to bone union. The unconventional method of leaving the IM pin protruding from the skin did not lead to complications. All of the owners, contacted from one to two months after removal of the implants, reported their animals to have excellent or good results. Five animals were lost to follow-up.
Keywords: External skeletal fixation; IM pin; fracture fixation